Fault Tolerance in WSN Through Uniform Load Distribution Function - Mohapatra, Hitesh; Rath, Amiya K. (International Journal of Sensors Wireless Communications and Control, 2021)
Aim: The existing cluster-based energy-efficient models such as Low Energy Adaptive Clustering Hierarchy (LEACH) and Stable Election Protocol (SEP) unable for the distribution of sensor nodes uniformly during cluster formation. The non-uniform cluster distribution structure leads to rapid energy depletion and high energy consumption. So, this paper aims to create uniform load-based cluster formation. Background: This proposed idea is generated from the famous saying
Keywords: fault tolerance